Exploring Vocabulary Learning Strategies Employed by PSDKU Aru Students - Jomima Ngosiem, Maria; Maruanauya, Hendrik; Tanasale, Inggrit (MATAI: International Journal of Language Education, 2025)
This research aims to recognize common vocabulary learning strategies (VLS) and find out the factors that affect the selection and effectiveness of vocabulary learning strategies among sixth-semester English students at PSDKU Aru. The methodology that the researcher used is a mixed method with the questionnaire and interview as the instruments. The questionnaire, used only to identify the VLSs that students commonly use, was adapted from Schmitt's VLS taxonomy (1997). The interview questions are open-ended and focus on VLSs, the factors that influence VLSs, and the difficulties in learning VLSs. The results of this research explained that the most common VLSs that students used were using a dictionary, asking classmates for the meaning, working and practicing with peers/in groups, using English language media (songs, movies, etc.), creating a vocabulary notebook, listening to music with word lists, remembering words through projects, and writing the words on paper and sticking them on the walls of their houses. Most of these commonly used strategies are consolidation strategies, which aim to memorize and become familiar with the words. Furthermore, the results also showed that there are two important factors that influence their choice of strategies for learning vocabulary. These factors are motivation and belief. These factors not only help in the choice of strategies that are good for them but can also affect the consistency of learning. Besides that, using one VLS may encourage students to utilize other VLSs. As a result, these findings provide lecturers and students with information regarding alternate strategies for teaching and learning language in class.